Collective Action Kelompok Sadar Wisata (Pokdarwis) dalam Percepatan Pariwisata Desa Labuan Kertasari untuk Peningkatan Ekonomi Masyarakat - Ilham Zitri (Jurnal Pemerintahan dan Politik Lokal, 2022)
Improving the village economy is very important, so the development and development of the existing tourism sector must be carried out immediately. Given the development and development of tourism has an important role in improving the economy of the community. Some of the roles or benefits of tourism development include: Increasing business opportunities, opening up employment opportunities, increasing community and government income, encouraging regional development, preserving culture and customs, increasing community intelligence, improving health and freshness and reducing social conflicts. This study uses a combination method (Mixed Methods). Combination Research Methods is a research method that combines quantitative and qualitative methods. combination research method is an approach in research that combines or connects quantitative and qualitative research methods. Existing tourism in Labuan Kertasari Village has not provided a high economic impact for the village community, this is because the existing tourist attractions are not well managed, the lack of resources that understand tourism is the basis for the unmanaged tourism. Factors that hinder the development of tourism in Labuan Kertasari Village, First Internal Factors: The quality and quantity of human resources in the field of tourism and culture is still lacking, Awareness of some tourism service business entrepreneurs and the community is still low to maximize tourism supporting facilities, There are still limited funds to build facilities needed by tourists, for example beach chair facilities needed by tourists, and this hinders the development of tourism.